2004
DOI: 10.18388/abp.2004_3558
|View full text |Cite
|
Sign up to set email alerts
|

Can transforming growth factor-beta1 and retinoids modify the activity of estradiol and antiestrogens in MCF-7 breast cancer cells?.

Abstract: Retinoic acid and transforming growth factor-beta (TGF-beta) affect differentiation, proliferation and carcinogenesis of epithelial cells. The effect of both compounds on the proliferation of cells of the hormone sensitive human breast cancer cell line (ER+) MCF-7 was assessed in the presence of estradiol and tamoxifen. The assay was based on [3H]thymidine incorporation and the proliferative activity of PCNA- and Ki 67-positive cells. The apoptotic index and expression of the Bcl-2 and p53 antigens in MCF-7 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Melatonin can up‐regulate TGFβ1 mRNA expression in MCF‐7 cells [22]. Moreover, melatonin‐inhibitory effect on breast cancer growth should be viewed as a TGFβ1‐dependent process and it can be completely prevented by adding anti‐TGFβ1 antibodies [14, 23]. In our study melatonin induced a significant rise in TGFβ1 levels in MCF‐7 cells after 72 hr and an evident growth‐inhibitory action can be documented only after this period.…”
Section: Discussionmentioning
confidence: 53%
“…Melatonin can up‐regulate TGFβ1 mRNA expression in MCF‐7 cells [22]. Moreover, melatonin‐inhibitory effect on breast cancer growth should be viewed as a TGFβ1‐dependent process and it can be completely prevented by adding anti‐TGFβ1 antibodies [14, 23]. In our study melatonin induced a significant rise in TGFβ1 levels in MCF‐7 cells after 72 hr and an evident growth‐inhibitory action can be documented only after this period.…”
Section: Discussionmentioning
confidence: 53%
“…Doxorubicin (DOX), a first generation anthracycline, is currently one of the most active drugs in the treatment of breast cancer. It exerts its action by altering the activity of topoisomerase II and inhibiting the DNA-dependent DNA and RNA synthesis [1]. DOX affects each phase of cell cycle, especially the S phase [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al [16] described that the combination therapy of ATRA with anthracyclines achieved 85% long-term survival rate in acute promyelocytic leukemia patients. Simultaneously, in the treatment of breast cancer, Czeczuga-Semeniuk et al [1] and Toma et al [17] reported that compared to estradiol and tamoxifen, the combination of ATRA and DOX was more effective to decrease the percentage of proliferating MCF-7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the K i -67 reduction in the Dox and Dox-CMC- h -BN-treated U87-MG cells has been attributed to an inhibited proliferation of these cells. Since the Dox molecules naturally intercalate into the DNA double helix structure, they block the cell cycle at S or G2/M phase . A study performed on breast cancer patients indeed indicated the K i -67 reduction in case the cell cycle was arrested at the G2/M phase …”
Section: Discussionmentioning
confidence: 99%